PROCEDURES FOR PROVIDING OPERATIONAL ASSISTANCE FOR FAMILY PLANNING AT THE POPULATION CONTROL AND FAMILY PLANNING SERVICE OF EAST BOLAANG MONGONDOW REGENCY - Vaykel Marshel Mokobimbing; Ferdinand Kerebungu; Recky H. E. Sendouw (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to determine, describe, analyze and interpret the procedure for providing Family Planning Operational Assistance (BOKB) at the Population and Family Planning Control Office of East Bolaang Mongondow Regency and identify the determinant factors that influence the procedure for providing BOKB. This study uses a qualitative approach. Data collection was carried out by means of interviews, observation and documentation. The results of the study indicate that the procedure for providing family planning operational assistance (BOKB) at the Population and Family Planning Control Office of East Bolaang Mongondow Regency has not been fully implemented optimally because there are still procedures that are not as in the SOP, namely delays in disbursement of funds, the ability of implementers in compiling documents, verification of recipient lists experiencing time and human resource limitations as well as geographical conditions in remote areas, the determination of recipient lists is not optimal in terms of transparency and information delivery to the community, the processing of BOKB funds is limited in administrative capabilities and human resources as well as error network access and determinant factors that influence such as the coverage of active KB participants and the number of PUS, the performance of field officers/PLKB, geographical location, implementation performance and budget realization.